O ensino de robótica educacional por meio de metodologias ativas: um estudo fenomenológico sobre os desafios e possibilidades na prática pedagógica do professor - Fernandes, Richard (2019)
By presenting an inter / multidisciplinary knowledge base, educational robotics, when worked by the teacher through active methodologies, makes it possible to undertake a student-centered pedagogical practice. From this perspective, this qualitative research aims to interpret the challenges and possibilities in the insertion of Educational Robotics through Active Methodologies in the teacher's pedagogical practice. The epistemological assumptions that underlie this phenomenological research are grounded above all in the epistemological discussions of Papert (1994), Campos (2017), Martins (2006) Bacich and Moran (2018), Sancho (2006), Freire (1996), Carvalho Neto (2018), Heidegger (2005) and Forghieri (2019). As a methodological procedure, the phenomenological method of investigation can be used in this research. Thus, the process of data construction in the research locus was based on the application of semi-structured interviews, semi-structured questionnaires and systematic observation with four teachers who work in a public school in the municipal education system in Caraúbas-RN. At first, even before applying the research instruments to the subjects of this research, we promoted two weeks of training in educational robotics through active methodologies. After this experience, we began to interpret - under the perspective of phenomenology - the speech reverberated by the teachers. Through the interpretation of the data, it was found that the teacher when working with educational robotics through active methodologies in the classroom has the chance to promote for students a hybrid, flexible and groundbreaking pedagogical practice. On the other hand, it was evident that, besides the teachers participating in this research have experienced for the first time the experience of teaching and learning with educational robotics, today, there are several challenges for school institutions to insert educational robotics through methodologies. active in pedagogical practice, such as: lack of public policies for this field of knowledge, little publicity within the institutions to clarify teachers what educational robotics really is, lack of didactic-pedagogical knowledge on the part of teachers to know how to work with Educational robotics in the classroom with students. After these findings, it is expected that this research can contribute to the increase of educational robotics in the school curriculum of institutions.